DEIKSIS DALAM FILM BRAVEHEART KARYA RANDALL WALLACE: SUATU ANALISIS PRAGMATIK - Dengah, Lavina Agatha (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACTS Pragmatics is the study of the relations between language and context that are basic to an account of language understanding. The single mostobviousway in which the relationshipbetween languageand contextis reflectedin the structures ofthe languages​​themselves, is through the phenomenon ofdeixis.The objective of this research are to identify the types of deixis and to analyse the usage of deixis in the film. The method used in this research is descriptive method. The identification and analysing data describe descriptively. In analysing data the theory of Levinson is used. He categorized deixis  into five types, those are person deixis, place deixis, time deixis, discourse deixis, and social deixis. Levinson also distinguishes two kinds of deixis usages, namely gestural and symbolic usage. The result shows  that there are five types of deixis in the film Braveheart, those are person deixis, place deixis, time deixis, discourse deixis, and social deixis, wheares the usage of deixis found in the film are symbolic and gestural usage. It is expected that this research will help the students and the other readers in learning the pragmatic aspects, especially about deixis. Keyword: Deixis;BraveheartFilm; Pragmatics